FORMULASI STRATEGI UNTUK PENGEMBANGAN PASAR INDUSTRI SEMEN DI JAWA TIMUR - Naufal, Aulia Fajar; Achmadi, Fuad (BISMA: Jurnal Bisnis dan Manajemen, 2017)
Abstract:The cement industry is facing a new business era as more cement producers joining the domestic market competition that causesthe shift on the existing cement consumption map. This research aims to identify the companyâ€™s internal and external factors and to formulate best alternative strategy for the company â€œAâ€ in facing the market competition in East Java Province. The strategy is formulated by using Strengths Weaknesess Opportunities andThreats(SWOT) analysis, Strategic Position and Action Evaluation (SPACE) and Grand Strategy (GS)matrix continuedby Quantitative Strategic PlanningMatrix (QSPM). Results show thatthe company should use aggressive strategy focusing on market penetration, aggressive promotion, increased selling power, and product development in order to expand the market in East Java Province. Keywords: Strategy Formulation, SWOT Analysis, SPACE, GS Matrix, QSPM.